Soil moisture as a key factor in carbon release from thawing permafrost in boreal forest ... - Song, Xiaoyan (Mendeley, 2019)
In this study, by quantifying the CO2, CH4 releases and the soil properties of moisture, SOC quantity and quality and microbial activities in a 239-day incubation experiment where the soil moisture was experimentally modified to simulate natural, drier and flooded condition, we tested the hypotheses 1) the C vulnerability in permafrost deposits would be higher than that in active layer soils; 2) C releases under aerobic conditions and their climate forcing would be greater than anaerobic condition, but aerobic C release would be constrained by drier condition; and 3) soil moisture would be the strongest factor influencing C release under aerobic condition, whereas anaerobic C release would be mostly related to microbial activities. ...